Characterizing death acceptance among patients with cancer. Issue 4 (10th March 2019) - Philipp, Rebecca; Mehnert, Anja; Lo, Chris; Müller, Volkmar; Reck, Martin; Vehling, Sigrun
Abstract: Objective: Death acceptance may indicate positive adaptation in cancer patients. Little is known about what characterizes patients with different levels of death acceptance or its impact on psychological distress. We aimed to broaden the understanding of death acceptance by exploring associated demographic, medical, and psychological characteristics. Methods: At baseline, we studied 307 mixed cancer patients attending the University Cancer Center Hamburg and a specialized lung cancer center (age M = 59.6, 69% female, 69% advanced cancer). At 1‐year follow‐up, 153 patients participated. We assessed death acceptance using the validated Life Attitude Profile–Revised. Patients further completed the Memorial Symptom Assessment Scale, the Demoralization Scale, the Patient Health Questionnaire, and the Generalized Anxiety Disorder Questionnaire. Statistical analyses included multinomial and hierarchical regression analyses. Results: At baseline, mean death acceptance was 4.33 (standard deviation [SD] = 1.3, range 1‐7). There was no change to follow‐up ( P = 0.26). When all variables were entered simultaneously, patients who experienced high death acceptance were more likely to be older (odds ratio [OR] = 1.04; 95% confidence interval [CI], 1.01‐1.07), male (OR = 3.59; 95% CI, 1.35‐9.56), widowed (OR = 3.24; 95% CI, 1.01‐10.41), and diagnosed with stage IV (OR = 2.44; 95% CI, 1.27‐4.71). They were less likely to be diagnosed with lung cancer (OR = 0.20; 95% CI, 0.07‐0.58), and their death acceptance was lower with every month since diagnosis (OR = 0.99; 95% CI, 0.98‐0.99). High death acceptance predicted lower demoralization and anxiety at follow‐up but not depression. Conclusions: High death acceptance was adaptive. It predicted lower existential distress and anxiety after 1 year. Advanced cancer did not preclude death acceptance, supporting the exploration of death‐related concerns in psychosocial interventions.